The Net Discharge Mechanism of the VB2/Air Battery. Issue 1 (1st January 2015) - Stuart, Jessica; Hohenadel, Amelia; Li, Xuguang; Xiao, Han; Parkey, Jeff; Rhodes, Christopher P.; Licht, Stuart
Abstract : The electrochemical discharge of VB2 is a unique process that involves the multiple electron per molecule oxidation of the tetravalent transition metal ion, V (+4 → +5), and each of the two borons 2×B (−2 → +3), corresponding to a net 11 electron discharge mechanism of the VB2 /air cell as described by the overall cell reaction: VB2 + 11/4O2 → B2 O3 + ½ V2 O5 . However, in the presence of alkaline electrolytes, the discharge products include alkali salts associated with vanadaic and boric acid. In this study, we used FTIR, XRD, and coulombic efficiency measurements to probe the discharge products of high capacity cells and isolate KVO3 as the principal vanadium discharge product. Additionally, we show that K2 B4 O7 is the probable borate product. From FTIR analysis in KOH electrolyte, it is evident that the alkaline VB2 /air discharge reaction is: VB2 + 11/4O2 + 2KOH → ½ K2 B4 O7 + KVO3 + H2 O. XPS shows that the surface structure of nanoscopic VB2 is very different from macroscopic VB2, which may contribute to the improved electrochemical properties of the nanoscopic material. The understanding of the discharge process and factors affecting performance contribute to furthering the development of extremely high capacity VB2 /air batteries that utilize multi-electron processes.